Analysis of Ecstasy Tablets Using Capillary Electrophoresis with Capacitively Coupled Contactless Conductivity Detection1. Issue 6 (21st July 2014) - Porto, Suely K. S. S.; Nogueira, Thiago; Blanes, Lucas; Doble, Philip; Sabino, Bruno D.; do Lago, Claudimir L.; Angnes, Lúcio
Abstract A method for the identification of 3, 4‐methylenedioxymethamphetamine (MDMA) and meta‐chlorophenylpiperazine (mCPP) was developed employing capillary electrophoresis (CE) with capacitively coupled contactless conductivity detection (C4D). Sample extraction, separation, and detection of "Ecstasy" tablets were performed in <10 min without sample derivatization. The separation electrolyte was 20 mm TAPS/Lithium, pH 8.7. Average minimal detectable amounts for MDMA and mCPP were 0.04 mg/tablet, several orders of magnitude lower than the minimum amount encountered in a tablet. Seven different Ecstasy tablets seized in Rio de Janeiro, Brazil, were analyzed by CE‐C4D and compared against routine gas chromatography‐mass spectrometry (GC‐MS). The CE method demonstrated sufficient selectivity to discriminate the two target drugs, MDMA and mCPP, from the other drugs present in seizures, namely amphepramone, fenproporex, caffeine, lidocaine, and cocaine. Separation was performed in <90 sec. The advantages of using C4D instead of traditional CE‐UV methods for in‐field analysis are also discussed.